Attractiveness in Urban Design : A study of the production of attractive places - Hidman, Erik (Luleå tekniska universitet, Arkitektur och vatten, 2018)
This research project investigates the production of attractive places, through theory form and everyday life. The research study was originally sprung from practical questions regarding the extensive use of the term attractiveness in urban planning and design. What is the term intended to address? How is the term understood in local contexts? How is the term transformed to built environments? The term is rarely scrutinized and criticized and the understanding of the term, its meaning and implications is diverse. Starting from critical urban theory, the research project critically scrutinizes the term and contrasts it with local citizens perspectives of attractive towns. The research project proceeds from the idea of that places are produced not only by planning and urban design professionals, but also by people living in and visiting a place (Lefebvre, 1991). The research question addressed is How is the term attractiveness in built environments understood and designed in the perspectives of architects/urban designers and local citizens, and how can the term be explained to inform future planning of attractive urban environments? The research design consists of four sub-studies to investigate planning and local perspectives of attractiveness, its presentations and urban forms. The research design was set up in Kiruna and Gällivare, two mining towns in the sparsely populated Swedish north. These towns are undertaking major urban transformations due to the mining activities. Both municipalities explain the transformation processes as opportunities to become more attractive for people to settle as permanent residents. The term was investigated through discourse and qualitative content analysis, whilst the local citizen perspective was investigated through urban living labs. The conclusion was that the urban planning and design sphere of place production defines the term attractiveness according to their challenges. The term addresses the contemporary situation of place competition where places compete about ...